2019
DOI: 10.1186/s13660-019-1964-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrete majorization type inequalities for convex functions on rectangles

Abstract: In this paper, we present several discrete majorization type inequalities for the convex functions defined on rectangles. MSC: 26D15; 26B25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 47 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…There are many inequalities, which it would not be possible to establish without convex functions [28][29][30]. Some of the interesting inequalities that have been acquired by convex functions are the majorization inequality [21], Slater's inequality [31], Hermite-Hadamard's inequality [7], Jensen-Mercer's [32] inequality, and many more [33][34][35]. It has been confirmed that convex functions have played an important role in the development of the field of mathematical inequalities [36][37][38][39].…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many inequalities, which it would not be possible to establish without convex functions [28][29][30]. Some of the interesting inequalities that have been acquired by convex functions are the majorization inequality [21], Slater's inequality [31], Hermite-Hadamard's inequality [7], Jensen-Mercer's [32] inequality, and many more [33][34][35]. It has been confirmed that convex functions have played an important role in the development of the field of mathematical inequalities [36][37][38][39].…”
Section: Remarkmentioning
confidence: 99%
“…Due to the extensive applications and great importance of convex functions, this class has been generalized in various ways with the help of its characteristics and properties [16][17][18]. Some of the generalizations of convex functions are P-convex [19], s-convex [20], coordinates convex [21], h-convex [22], and 4-convex functions [23], etc. Among the above classes of convex functions, one of the significant classes is 6-convex functions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Dragomir [54] also provided the weighted version of the majorization inequality by taking certain tuples with relaxed majorization conditions. In 2019, Adil Khan et al [55] presented the extension of the classical majorization inequality and its weighted versions under different circumstances for convex functions on rectangles. Wu et al [56] acquired improvements of the majorization-type inequalities for convex functions through Taylor's theorem with a mean value form of remainder.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have been inventing the properties and applications of strongly convex function for more information, [5][6][7][8][9][10]. In this paper we will use this definition for normed space R.…”
Section: Introductionmentioning
confidence: 99%